Assessment of Buffalo Bull Semen Quality Based on Sperm Motility Parameters, Motion Characteristics and In Vitro Fertilization Rate - A. Sohail, S. M. H. Andrabi1, M. Anwar1, L. Ali and A. Mehmood1* (Pakistan Veterinary Journal, 2013)
The objective of the present study was to determine the prognostic value of sperm motility parameters and motion characteristics to predict in vitro fertilization (IVF) rate in the buffalo. Sperm motility parameters (%; motile, progressive, rapid and medium) and motion characteristics (path velocity = VAP, µm/sec; progressive velocity = VSL, µm/sec; curvilinear velocity = VCL, µm/sec; amplitude of lateral head = ALH, µm and beat cross frequency = BCF, Hz) of 5 buffalo bulls (Tag # 2, 4, 6, 11 and 12) were determined by Cell Motion Analyzer (CASA) at post dilution (PD), pre freezing (PF) and post thaw (PT) stages. IVF ability of individual bull was determined by cleavage rate (CR, %). Multiple regression analysis was used to determine the prognostic values of sperm motility parameters and motion characteristics for CR as a dependent variable. At PT, Bull 2 showed the highest (P<0.05) progressive and rapid motility, and VAP, VSL and VCL values as compared to other bulls. Data of CR (%) were similar among the five buffalo bulls. However, the prognostic value to predict the cleavage rate by the equation of motility and motion characteristics accounted for 81% (P=0.01). In conclusion, although at PT, Bull 2 showed the highest sperm progressive and rapid motility parameters, and motion characteristics (VAP, VSL and VCL) as compared to other bulls, but the CR was similar. The prognostic value by the equation of motility and motion characteristics accounted significantly to predict the CR.